Pengontrolan Diet Pasien Yang Didiagnosis Dengan Diabetes Mellitus Sebagai Dasar Program Konseling - Mutmainna, Amriati (Window of Health : Jurnal Kesehatan, 2020)
Diabetes is a serious life-long health condition that occurs when the amount of glucose in the blood is too high. The purpose of this study was the assessment of the dietary control of patients with diabetes mellitus to proposed a counseling program. The descriptive survey research design was used. Seventy-two (72) respondents were taken as subjects. The frequency and percentage, weight mean, and chi-square were used to treat quantitative data. Assessment rating for the dietary control ranges from â€œvery high degreeâ€ to â€œlow degreeâ€. There is no significant difference of the dietary control according to age, gender, and history of smoking. But then, there is a significant difference on the dietary control of participants when grouped according to blood sugar levels and body mass index. The assessment of this dietary control is considered to be an effective approach to address diabetes mellitus patients varied conditions through a counseling program.